Inherent Adaptive Structures Using Nature-Inspired Compound Elements - Chenaghlou, Mohammad Reza; Kheirollahi, Mohammad; Abedi, Karim; Akbari, Ahmad; Fathpour, Aydin (Frontiers in Built Environment, 2020)
Biomimicry studies have attracted significant attention in research and practice leading to effective engineering solutions to develop new types of structures inspired by natural systems. The objective of this study is to employ natural structures inherent adaptivity under changing loading conditions. Three new types of compound elements are proposed which are able to improve the structure load-bearing capacity through passive inherent adaptivity. A self-centering system, inspired by the human spine, which comprises a column pre-stressed through cables is employed as a kinematic isolator. A similar self-centering system is applied to increase the load-bearing capacity of unreinforced masonry columns. An axially loaded element, inspired by the Bamboo stem, which comprises a steel core reinforced by a series of cylindrical plates that are encased in a steel tube, is employed to control the onset of instability in long-span truss structures. Application to typical frame, masonry and truss structures is investigated through finite element analysis. Results have shown that the proposed compound elements are effective to increase the structure load-bearing capacity and to reduce the response under seismic excitation owning to their inherent adaptive features.